2014
DOI: 10.2460/ajvr.75.6.554
|View full text |Cite
|
Sign up to set email alerts
|

Use of an inverse dynamics method to compare the three-dimensional motion of the pelvic limb among clinically normal dogs and dogs with cranial cruciate ligament–deficient stifle joints following tibial plateau leveling osteotomy or lateral fabellar–tibial suture stabilization

Abstract: Gait characteristics of the pelvic limb did not differ between dogs that underwent TPLO and dogs that underwent an LFS procedure for CCL repair and were similar to those of clinically normal dogs. Both TPLO and LFS successfully provided long-term stabilization of CCL-deficient stifle joints of dogs with minimal alterations in gait.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Many recent studies have shown surgical stabilization to be effective in managing cranial cruciate ligament insufficiency (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). While there are numerous options for surgical management, surgery is not always an option.…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have shown surgical stabilization to be effective in managing cranial cruciate ligament insufficiency (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). While there are numerous options for surgical management, surgery is not always an option.…”
Section: Introductionmentioning
confidence: 99%
“…Three‐dimensional evaluation of joint stability is a contemporary method to evaluate joint kinematics for purposes of diagnosis and treatment efficacy . It is also important to assess joint stability under conditions intended to replicate joint dynamics during the normal step cycle as exemplified by quantification of angular displacement during application of translational force to the tibia performed in this investigation .…”
Section: Discussionmentioning
confidence: 99%
“…The ideal amount of initial graft tension for canine CrCL reconstruction is unknown, and there is a broad range, 20‐80 N, reported for human ACL reconstruction . The overarching goal is to apply the lowest tension to stabilize the joint, and avoid graft damage or vascular compromise . The process is complicated by the fact that the tensile force applied to the graft is not fully transferred intra‐articularly, and tensions vary among graft types and fixation devices .…”
Section: Discussionmentioning
confidence: 99%
“…Kinematics analysis of canine gait has therefore increasingly been used to quantify breed specific biomechanical characteristics [1,2], to explore the pathomechanics in relation to orthopedic disorders [3,4], and to evaluate treatment outcomes [5,6]. While several methodologies and equipment have been developed for kinematic analysis in canine patients, [2,[7][8][9], skin marker-based motion analysis and computed tomography (CT) modelbased fluoroscopic analysis are the most frequently used approaches in canine gait assessment [2,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…MKO offers the advantage that it can be implemented with conventional 3-D marker sets and therefore could provide a possible alternative for STA compensation in canine motion analysis. While MKO has been reported to be available for canine kinematics analysis after model modification for accommodating the dog conformation [9], its performance in the determination of STA-free joint kinematics has never been evaluated.…”
Section: Introductionmentioning
confidence: 99%